2010
DOI: 10.1149/1.3499217
|View full text |Cite
|
Sign up to set email alerts
|

Copper CMP Modeling: Millisecond Scale Adsorption Kinetics of BTA in Glycine-Containing Solutions at pH 4

Abstract: Millisecond scale benzotriazole (BTA) adsorption kinetics in acidic aqueous solution containing 0.01M glycine and 0.01M BTA have been investigated. Chronoamperometry was used to measure current densities on the surface of a micro-copper electrode in pH 4 aqueous solutions containing 0.01M glycine with or without 0.01M BTA. In the presence of BTA the current density decreased as the inverse of the square root of time for a few seconds due to adsorption of BTA. At potentials above 0.4V saturated calo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 47 publications
1
27
0
Order By: Relevance
“…Despite the difference in the magnitude of the oxidation rates for the two types of electrode, the intrinsic mechanism for passivation would be unchanged. Therefore, the approach used by Choi et al 3 of considering the fractional coverage of the copper by Cu(I)BTA complexes as a function of time was adopted to examine the material removal efficiencies from the measured current densities. Figure 6 shows the average steady-state current densities of copper during polishing with different down pressures or sliding velocities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the difference in the magnitude of the oxidation rates for the two types of electrode, the intrinsic mechanism for passivation would be unchanged. Therefore, the approach used by Choi et al 3 of considering the fractional coverage of the copper by Cu(I)BTA complexes as a function of time was adopted to examine the material removal efficiencies from the measured current densities. Figure 6 shows the average steady-state current densities of copper during polishing with different down pressures or sliding velocities.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the following analysis, a fraction of a monolayer of the protective material is assumed to be formed on the surface of copper during CMP, on the basis of the findings of Choi et al 3 A complete monolayer of protective material is taken as a coverage ratio of unity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Choi et al subsequently suggested that at steady state during CMP using an acidic slurry containing benzotriazole (BTA) and glycine, (Cu(I)BTA and Cu(II)BTA 2 ) form only a fraction of a monolayer on average, partly protecting the surface of a wafer from dissolution. 11 In this model, removal of the passive layer contributed only a small portion of the electrochemically measured MRR; most of the electro- † Deceased.…”
mentioning
confidence: 99%